Pemodelan kinetika pengeringan buah amla (Indian gooseberry) - Auliyaa Raaf; Farid Mulana; Yanna Syamsuddin; Nanda Suriaini; Muhammad Dani Supardan (Agroindustrial Technology, University of Trunojoyo Madura, 2024)
Amla fruit is not consumed directly because it has a sour and astringent taste, so it is widely used in various forms of dried and processed products for ease of use. Therefore, post-harvest handling of amla fruit as well as drying process is necessary. This study investigates the effect of drying method and sample thickness on the drying kinetics of amla fruit. In this study, amla was dried by sun drying and oven drying (at 40, 60 and 60°C) and sample sizes (1×0,5×0,5) cm and (1×1×0,5) cm. The results showed that the drying method and thickness of the sample affected the drying time. The shortest drying time was obtained from oven-dried samples at a drying air temperature of 60℃ and samples with smaller sizes (slice I). The semi-theoretical and empirical models were evaluated in amla fruit's drying kinetics. The fit of the model with the experimental data is determined using the coefficient determination (R2). Model Midili et al. give the best match with the highest R2 value. The effective moisture diffusivity at various drying conditions ranged from 5.747 × 10-10 to 1.242 × 10-9 m2/s for slice I and 4.522 × 10-10 to 9.213 × 10-10 m2/s for slice II. The effective moisture diffusivity is correlated with temperature using the Arrhenius equation. The activation energy needed to remove moisture from the amla fruit matrix was 20.230 kJ/mol for slice I and 22.006 kJ/mol for slice II. This kinetic study is useful for predicting the drying process yield and designing the dryer.